Sikap Ilmiah Mahasiswa pada Perkuliahan Lingkungan Berbasis Penelitian Perubahan Iklim melalui Google Classroom - Marlina, Reni; Melati, Husna Amalya; Oktavianty, Erwina; Ariyati, Eka; Maulidi, Andri (Universitas Sebelas Maret, 2018)
This study describes attitude of students on climate change research based lecture through google classroom. This research is a qualitative research with survey method to 90 students from physics education program, biology education and chemical education that take environment-based course. The instrument used in this study is attitude questionnaire. Data analysis using descriptive statistical analysis technique that is by using formula percentage. Based on the data analysis, it is found that the students give positive response to the environment study based on climate change research through google classroom. So that the utilization of google classroom on lecturing environment based on climate change research results provide a positive influence for learning activities.